Nice work if you can get it: the mercurial career of creative industries policy. (1st January 2007) - Andrew Ross,
Abstract : Driven by the belief that culture-based enterprise can be promoted as a driver of economic development, governments all over the world have developed policies aimed at boosting their creative industries. These policies ought to present some new, long-term opportunities for cultural workers, but in practice they seem more likely to universalise the traditionally precarious work profile of artists. Focusing on the career of creative industry policy in the UK, the USA and China, this paper calls for an assessment of its model of job creation from the standpoint of quality of work life.